2018
DOI: 10.5216/rpt.v47i1.52259
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Intestinal Parasites and Socioeconomic Evaluation of a Country Town in the Serra Gaucha Region, Rio Grande Do Sul, Brazil

Abstract: Worms are a serious public health issue in Brazil, easily transmitted in school-age children.To evaluate the prevalence of intestinal parasites and socioeconomic conditions in students in Ipê city, the children's guardians filled in a questionnaire to evaluate their knowledge about parasitosis and basic sanitary conditions; then, feces were analyzed with sedimentation and centrifugation-fluctuation techniques. Out of 124 analyzed samples, a positivity rate of 8.1% was observed, with the presence of Entamoeba c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 19 publications
1
5
0
Order By: Relevance
“…Waste collection carried out by public services also contributed to low occurrence of G. lamblia in the population under study. This correlation was also reported by other studies (Visser et al, 2011;Zanotto et al, 2018); it may be explained by the fact that waste can contain infecting forms of parasites, such as disposable diapers and toilet paper, attract animals and insects and generate environmental pollution. It may even be related to parasitic contamination of vegetable gardens, which was another variable that exhibited relation with positive cases found in this study (p=0.02).…”
Section: Discussionsupporting
confidence: 83%
“…Waste collection carried out by public services also contributed to low occurrence of G. lamblia in the population under study. This correlation was also reported by other studies (Visser et al, 2011;Zanotto et al, 2018); it may be explained by the fact that waste can contain infecting forms of parasites, such as disposable diapers and toilet paper, attract animals and insects and generate environmental pollution. It may even be related to parasitic contamination of vegetable gardens, which was another variable that exhibited relation with positive cases found in this study (p=0.02).…”
Section: Discussionsupporting
confidence: 83%
“…The prevalence of intestinal parasites found in this study, corresponding to 8.1%, was equal to another study conducted in the city of Sananduva, RS, where 8.1% (44/546) of individuals presented positive results for parasites, and the most frequent structures were E. nana and E. coli cysts, found in 44.4% and 24.4% of fecal samples respectively (Bellin & Grazziotin, 2011). Similarly, another study evidenced the same prevalence of 8.1% (10/124) in individuals from Ipê municipality, also located in RS (Zanotto et al, 2018). A lower prevalence was found in the city of Bento Gonçalves, RS, corresponding to 5.3% (96/1808), where the most prevalent parasites were E. nana, Giardia intestinalis and E. coli (Ferlito & Dalzochio, 2020).…”
Section: Discussionmentioning
confidence: 64%
“…Distribution of intestinal parasites based on type of hand washing material was carried out and data revealed that there were three kinds of agents used by children after using washroom. Soap and water, soil and water and only water 16 . It was found that most of the positive cases linked to children that wash their hands with only water.…”
Section: Discussionmentioning
confidence: 99%